The impact of virtual reality meditation on college students’ exam performance - Kaplan-Rakowski, Regina; Johnson, Karen R.; Wojdynski, Tomasz (Smart learning environments, 2021)
Advocates of meditation claim that it can improve various aspects of life, including health, attention, thinking, and learning. The purpose of this empirical, quantitative, between-subject study was twofold. First, it compared the effectiveness of meditation delivered through virtual reality versus video, as measured by students’ test scores. Second, the study provided insights on the use of meditation, whether via virtual reality or video, as a way to positively affect well-being. T -test analysis showed virtual reality meditation to be significantly more beneficial than video meditation. Students reported that meditation techniques delivered using either medium to be helpful in decreasing their pre-exam anxiety. This study has practical implications and offers evidence on the beneficial impact of VR meditation on students’ exam performance and anxiety levels.